2021
DOI: 10.1002/adsc.202001117
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Z‐Selective Olefin Metathesis Reactions by Molybdenum, Tungsten, Ruthenium, and Vanadium Catalysts

Abstract: This review article summarizes reports for Z‐selective olefin metathesis reactions by molybdenum, tungsten, ruthenium, and vanadium catalysts. It is clearly demonstrated that the ligand modifications play essential roles in achieving the stereospecific olefin metathesis reactions. In particular, Mo‐ and W‐alkylidene based complex catalysts having pyrrolide‐aryloxide [or bis(aryloxide)] were highly effective in the efficient enantioselective ring opening/cross‐metathesis (EROCM), cross metathesis (CM), homodime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 144 publications
0
29
0
Order By: Relevance
“…Separating the target product from its undesired isomer is costly, wasteful, and sometimes impossible. The most direct, atom-economic, and elegant solution is offered by catalysts that enable selective synthesis of the singleisomer target [33,[35][36][37]. However, design of such catalysts is challenging.…”
mentioning
confidence: 99%
“…Separating the target product from its undesired isomer is costly, wasteful, and sometimes impossible. The most direct, atom-economic, and elegant solution is offered by catalysts that enable selective synthesis of the singleisomer target [33,[35][36][37]. However, design of such catalysts is challenging.…”
mentioning
confidence: 99%
“…Our calculation study showed that E-isomer 22a was thermodynamically more stable than (Z)-isomer (ΔG = 2.2 kcal/mol), which may account for the observed experimental result. Notably, based on some inspiring works, we also attempted to invert the Z/E selectivity of the reaction by using the (Z)-selective Grubbs' catalysts 46 [48][49][50][51]. However, we did not obtain the desired product, and the starting material was recovered in most cases.…”
Section: Scheme 6 Exploration Of the Rcm Reactionmentioning
confidence: 99%
“…[23][24][25] Several valuable metals, such as palladium, ruthenium, rhodium, gold, silver, copper, nickel, cobalt, platinum, iridium, indium, cerium … etc, were incorporated as powerful catalysts in modern organic syntheses and heteroannulations. [26][27][28][29][30][31][32][33][34][35][36][37][38] The unique catalytic activities of such metals inferred from the presence of occupied d-or f-orbitals. For example, palladiumcatalyzed carbon-carbon coupling reactions are the fundament for the synthesis of fine chemicals, such as pharmaceuticals and agricultural compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Multicomponent reactions (MCRs) are reported as ideal tool for organic synthesis due to their widely use for the fast formation of molecules for high‐tech applications, and they are characterized by operational simplicity, atom economy, bond forming efficiency, and quick access to molecular complexity from simple starting materials [23–25] . Several valuable metals, such as palladium, ruthenium, rhodium, gold, silver, copper, nickel, cobalt, platinum, iridium, indium, cerium … etc, were incorporated as powerful catalysts in modern organic syntheses and heteroannulations [26–38] . The unique catalytic activities of such metals inferred from the presence of occupied d‐ or f‐orbitals.…”
Section: Introductionmentioning
confidence: 99%